Model pembelajaran pendidikan jasmani manajemen di era pandemi covid-19: Tinjauan literatur - Khamidi, Amrozi; Hartoto, Setiyo (Universitas Nusantara PGRI Kediri, 2022)
The Covid-19 pandemic brings very complex problems to implementing education and learning in schools. Physical education subjects are one of the many subjects that must make adjustments to the Covid-19 pandemic. Physical education materials need to be studied how learning can be done to carry out the learning process in accordance with government regulations. This research aims to provide information about the management of physical education learning in the era of the Covid-19 pandemic. This research uses literature review methods by using comprehensive strategies such as searching for articles in a database of research journals. The databases used are Pubmed/MEDLINE, Scopus, Web of Science, and Embase. The keywords used in the search are learning models in the era of the Covid-19 pandemic and physical education. A total of 20 articles in the last ten years on used as data and analyzed. Based on the results and discussion of the principles of the management of physical education and model physical education in the era of pandemic covid-19. This study is carried out in the future to understand the learning process that can be done during the Covid-19 pandemic, especially in physical education.